Latest Advances on Bacterial Cellulose-Based Antibacterial Materials as Wound Dressings - Zheng, Lu; Li, Shanshan; Luo, Jiwen; Wang, Xiaoying (Frontiers in Bioengineering and Biotechnology, 2020)
At present, there are various wound dressings that can protect the wound from further injury or isolate the external environment in wound treatment. Whereas, infection and slow self-healing still exist in wound healing process. Therefore, it is urgent to develop an ideal wound dressing with good biocompatibility and strong antibacterial activity to promote wound healing. Bacterial cellulose is a kind of promising biopolymer because it can control wound exudate and provide a moist environment for wound healing. However, the lack of antibacterial activity limits its application. In this paper, the advantages of bacterial cellulose as wound dressings were introduced, and the preparation and research progress of bacterial cellulose- based antibacterial composites in recent years were reviewed, including adding antibiotics, combining with inorganic antibacterial agents or organic antibacterial agents. Finally, the existing problems and future development direction of bacterial cellulose-based antibacterial wound dressings were discussed.